Sistem Informasi Peminjaman dan Pengembalian Rekam Medis Berbasis SMS Gateway - Eltigeka Devi Apriliani; Sustin Farlinda; Feby Erawantini; Mochammad Choirur Roziqin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The process of borrowing and returning medical record at Ambulu Public Health Center still use manual book and make return of medical record documents that are not in accordance with SOP (Standard Operational Procedure). The purpose of this research is to design and create an information system of borrowing and returning the medical records based SMS gateway at Ambulu Public Health Center. The method used in this research is waterfall. The stages of the waterfall is requirements analysis, system design, create system, and system testing. The data collected by interview, observation, and FGD (Focus Group Discussion). The results of this research is the information systems of borrowing and returning the medical records based SMS gateway as message or automatic reminder. The suggestion for Ambulu Public Health Center is use information system of borrowing and returning the medical record based SMS gateway can make simple the reports.